Unity networking fundamentals : creating multiplayer games with Unity - Kelly, Sloan (Apress L.P., 2022)
Learn the fundamentals of networking with Unity and C#. This book covers a variety of topics, including accessing data using RESTful APIs, local networked games, and creating multiplayer online games using client-server architecture. The book provides the basics of networking, sockets, TCP vs. UDP, client-server architecture, serialization, RESTful APIs, network latency, and client-side prediction. Projects are presented to illustrate the concepts, including a chat client/server overlay for your game, and a 3D maze game that allows up to four players to connect over the network. By the end of the book, you will be familiar with low-level networking concepts such as protocols and architecture as well as high-level knowledge on how to create applications that use a client/server architecture for multiplayer games. What You Will Learn Know the difference between TCP and UDP, and the pros and cons of these protocols Create client-server multiplayer games in Unity using C# Receive and process data from a remote server using RESTful APIs Understand latency and how to mitigate its impact Who This Book Is For Readers familiar with Unity and C# development who want to create multiplayer games.